WHAT IS THE ROLE OF TEACHER'S INTONATION AND WORD STRESS IN MAKING SUCCESSFUL SPEECH? - Qambarova Mohlaroyim (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Effective communication is the cornerstone of successful speech, and teachers play a vital role in instilling this skill in their students. Among the various factors that contribute to successful speech, intonation and word stress are two crucial elements that are often overlooked. A teacher's intonation and word stress can significantly impact the way students perceive and process spoken language, ultimately influencing their ability to communicate effectively. This article will explore the role of teacher's intonation and word stress in making successful speech, highlighting their importance in language acquisition, comprehension, and overall communication.